Observation and analysis of kink effect during drain current inception of GaN HEMT. (August 2018) - Bag, Ankush; Das, Subhashis; Mukhopadhyay, Partha; Biswas, Dhrubes
Abstract: Drastic change of drain current has been measured with drain voltage at the inception when there is a transition from OFF to ON state for two-dimensional electron gas at the AlGaN/GaN heterojunction on sapphire substrate. Hysteresis in the drain current characteristics has also been observed when drain bias has been traced back to zero at certain gate bias during this transition. Both horizontal and vertical energy band diagrams have been incorporated along with electric field contour mapping of the device to explain the related electron and hole transport physics. These nanoscale phenomena are the combined effect of energy barrier modulation due to both the drain and gate bias in presence defect related fabrication anomalies. Therefore, different possible transport mechanisms such as electron punch through, Fowler-Nordheim tunneling, impact ionization, hot-electron effect, trap assisted tunneling, de-trapping are discussed in correlation with the band diagrams. Graphical abstract: Image 1 Highlights: Drain current variations has been observed during transition of 2DEG channel from OFF to ON condition for PA-MBE grown AlGaN/GaN heterojunction. A sudden kink effect has been observed along with a hysteresis behavior. Hysteresis and kink effect are possibly attributed to trapped charges at AlGaN/GaN interface and Fowler Nordheim tunneling, respectively.